DECOMPRESSION BY THINNING-OUT A BEAK-TYPE OSSIFICATION OF THORACIC POSTERIOR LONGITUDINAL LIGAMENT, A CASE REPORT - S. Dohar A.L. Tobing; Ade Martinus (Journal of Global Pharma Technology, 2018)
Introduction: Ossification of posterior longitudinal ligament (OPLL) is commonly caused dysfunction of the spinal cord. The conservative therapy has been proved to be ineffective and surgical treatment is often needed. Accessing the anterior border of OPLL for anterior decompression while ensuring safe decompression of spinal cord are technical challenges for the treatment. The objectives of this case report is to introduce a surgical technique of decompression and decided whether it is an effective surgical technique to treat a beak type thoracic OPLL, especially in T9-10.Methods: We reported a male, 38 years old, who were admitted to Cipto Mangunkusumo hospital in 2016 and was diagnosed as paraparesis due to OPLL at the level of T9-10.Results and Discussion: Surgical decompression was performed from a posterior approach. The left facet, pedicle of T9, and the distal part of T9 vertebral body were removed using highspeed burr until the interval of calcified area was reached distally. Thinning of the calcified area was done until paper thin and expansion of the dura and spinal cord can be observed. The decompression procedure was followed by stabilization of T7-11 using pedicle screws and rods. No worsening of the neurological symptoms was observed post operatively. The patient could stand and assisted walk in day 3 post operation.Conclusion:. This surgical procedure has been shown to be an effective therapy and achieves satisfactory clinical outcomes for patients.Keywords: thoracic ossification of posterior longitudinal ligament, beak type thoracic OPLL, Surgical Treatment, decompression with posterior approach.